Micronekton diel migration, community composition and trophic position within two biogeochemical provinces of the South West Indian Ocean: Insight from acoustics and stable isotopes. (August 2018) - Annasawmy, P.; Ternon, J.F.; Marsac, F.; Cherel, Y.; Béhagle, N.; Roudaut, G.; Lebourges-Dhaussy, A.; Demarcq, H.; Moloney, C.L.; Jaquemet, S.; Ménard, F.
Abstract: Spatial distribution, community composition and trophic roles of micronekton (crustaceans, fishes and squids) were investigated in the Indian South Subtropical Gyre (ISSG) province and the East African Coastal province (EAFR), by combining acoustic surveys, mid-water trawls and stable isotope analyses from scientific cruises conducted in 2009 and 2010. Mesopelagic micronekton performed diel vertical migrations in both provinces, from deep (400–740 m) to surface (0–200 m) layers at dusk and in the opposite direction at dawn, with some species migrating below 740 m. The EAFR province was more dynamic than the oligotrophic ISSG province, with enhanced eddy activity and enhanced yearly productivity. The active enrichment mechanisms in the EAFR, in terms of available primary production, led to high micronekton acoustic density (as a proxy of micronekton abundance) and large micronekton weight and abundance estimates from trawl data. Particulate organic matter in the EAFR exhibited greater enrichment in 13 C and 15 N compared to the ISSG and, consequently, tissues of selected micronekton organisms in the EAFR were more enriched in 15 N (higher δ 15 N values). In both provinces, micronekton encompassed a wide range of isotopic niches, with large overlaps between species. Micronekton and swordfish in the EAFR had an overlapping range of δ 15 N values, contrasting with the ISSG province where swordfish were two trophic levels higher than the sampled micronekton. Our results provide some evidence that the combined action of riverine input and the dynamics of eddies might influence productivity in the EAFR, and hence the abundance of micronekton and the enrichment of tissues in 15 N, compared to the oligotrophic ISSG province. Highlights: The EAFR was more dynamic with enhanced eddy activity and more productive than the ISSG. Most mesopelagic micronekton performed diel vertical migrations in both provinces. Particulate organic matter and tissues of selected micronekton organisms were enriched in  15 N in the EAFR. Micronekton and swordfish had an overlapping range of δ 15 N values in the EAFR. In the ISSG, swordfish were 2 trophic levels higher than the sampled micronekton.